Respuesta :

gmany

Step-by-step explanation:

The point-slope form of an equation of a line:

[tex]y-y_1=m(x-x_1)[/tex]

m - slope

(x₁, y₁) - point on a line

We have the point (3, -3) and the slope m = -2. Substitute:

[tex]y-(-3)=-2(x-3)[/tex]

[tex]y+3=-2(x-3)[/tex] - point-slope form

Convert to the slope-intercept form (y = mx + b):

[tex]y+3=-2(x-3)[/tex]        use the distributtive property

[tex]y+3=-2x+(-2)(-3)[/tex]

[tex]y+3=-2x+6[/tex]      subtract 3 from both sides

[tex]y=-2x+3[/tex] - slope-intercept form

Convert to the standard form (Ax + By = C):

[tex]y=-2x+3[/tex]        add 2x to both sides

[tex]2x+y=3[/tex] - standard form

Convert to the general form (Ax + By + C = 0):

[tex]2x+y=3[/tex]      subtract 3 from both sides

[tex]2x+y-3=0[/tex] - general form